Adaptive Islamic Religious Education Learning for Quality Inclusive Education in Public Universities - Narulita, Sari; Ridwan Effendi, Muhamad; Amaliyah; Nyoman Padmadewi, Ni (Proceeding of International Joint Conference on UNESA, 2026)
The Islamic Religious Education Study Program (IRE) at Public Universities faces challenges in realizing inclusive learning, especially for students with visual impairments. Based on empirical data, the main obstacles for students with visual impairments include limited mobility orientation in the campus environment, difficulty accessing teaching materials, limited exam time, and a lack of opportunities to participate in student organizations. This article develops a simple adaptive learning by emphasizing these four aspects. The results show that strengthening mobility orientation skills, providing accessible teaching materials, increasing exam time, and supporting student organization participation can increase the involvement, independence, and learning achievement of students with visual disabilities